Operative and long‐term oncological outcomes in patients undergoing robotic versus laparoscopic surgery for rectal cancer. Issue 6 (24th September 2020) - Bilgin, Ismail Ahmet; Bas, Mustafa; Aytac, Erman; Benlice, Cigdem; Esen, Eren; Kirbiyik, Ebru; Kiziltas, Cansu; Aghayeva, Afag; Ozben, Volkan; Hamzaoglu, Ismail; Karahasanoglu, Tayfun; Baca, Bilgi
Abstract: Background: This study aimed to compare short‐ and long‐term outcomes after robotic versus laparoscopic approach in patients undergoing curative surgery for rectal cancer. Methods: Patients undergoing elective robotic and laparoscopic resection for rectal cancer were included. Perioperative clinical characteristics, postoperative short‐ and long‐term outcomes were compared between groups. Results: There were 72 and 44 patients in robotic (RG) and laparoscopic (LG) groups respectively. No differences were detected regarding patients' demographics, histopathologic outcomes, conversion rates and 30‐day overall postoperative complication rates. Operative time was longer in the RG (341 ± 111.7 vs. 263 ± 97.5 min, p = 0.001) and length of stay was longer in the LG (4.4 ± 1.9 vs. 6.4 ± 2.9 days, p = 0.001). The 5‐year overall and disease‐free survival rates were similar (97.1% and 94.9%, p = 0.78; 86.2% and 82.7%, p = 0.72) between the groups. Conclusion: This study showed both short and long‐term outcomes of a limited number of included patients between the robotic and laparoscopic surgery were similar. However, future studies and randomized trials are necessary to establish these findings.